Tayangan Video Animasi “Si Nopal” Untuk Mendukung Interaksi Sosial Siswa Sekolah Dasar - Ghafiruna Al Aziz; Chumi Zahroul Fitriyah; Zetti Finali (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2020)
Social interaction is a dynamic social relationship that involves relationships between individuals, between groups, and between individuals and groups. The purpose of this research is to analyse an animated film "Si Nopal" in supporting social interaction of the elementary students. The type and design of the study used in this study is descriptive research. The data collection methods are documentation and interviews. Qualitative data analysis used in this study consisted of three activity processes, namely data reduction, data presentation, and drawing conclusions. Based on the results and discussion it can be seen that the Nopal's animated video can support students' social interactions. The social interactions in the Nopal animated video include the communication process, social contact, and associative processes. Students who are given the animated video show "Si Nopal" have the motivation to imitate the aspects of social interaction in the video shown.